2012
DOI: 10.7314/apjcp.2012.13.6.2847
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Killing Effect of Osteosarcoma Cells by Cinobufacini and Cisplatin in Combination

Abstract: Purpose: To study the killing effects on osteosarcoma cells of cinobufacini and cisplatin in combination and the related mechanisms so as to explore the chemotherapeutic method with integrated traditional Chinese and Western medicines. Methods: Cinobufacini and cisplatin were applied to OS732 cells singly or jointly and survival rates were measured by MTT assay. Changes in cellular shape were observed with inverted phase contrast and fluorescence microscopy and apoptosis rates were analyzed with flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…In the past decade, the survival of patients with osteosarcoma has increased, due to rapid advances in neoadjuvant chemotherapy (Chano et al, 2004;Marina et al, 2004). Although combination of surgery with chemotherapy has noticeably improved the survival rate of osteosarcoma patients, the application of anticancer drugs is still associated with significant adverse reactions, for instance acquisition of drug-resistant phenotypes, necessitating the development of new chemotherapeutical agents (Huang et al, 2012;Choeyprasert et al, 2013). Recently, tumor therapy by traditional Chinese herb is becoming more and more attractive (Li et al, 2007;2008;Youns et al, 2009;Louis et al, 2012;Miron et al, 2012;Cheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, the survival of patients with osteosarcoma has increased, due to rapid advances in neoadjuvant chemotherapy (Chano et al, 2004;Marina et al, 2004). Although combination of surgery with chemotherapy has noticeably improved the survival rate of osteosarcoma patients, the application of anticancer drugs is still associated with significant adverse reactions, for instance acquisition of drug-resistant phenotypes, necessitating the development of new chemotherapeutical agents (Huang et al, 2012;Choeyprasert et al, 2013). Recently, tumor therapy by traditional Chinese herb is becoming more and more attractive (Li et al, 2007;2008;Youns et al, 2009;Louis et al, 2012;Miron et al, 2012;Cheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The present therapeutic strategies in clinical applications have low efficiency under the current osteosarcoma therapy (Huang et al, 2012;Choeyprasert et al, 2013). Therefore, new drugs for osteosarcoma therapy are urgently needed to explore.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have suggested a concept of dietary intervention which has gained popularity and wide acceptance [712]. Another approach that has gained importance is the use of biotoxins such as animal venoms as cancer therapeutic agents [1317]. These biotoxins are produced by living organisms as a defense mechanism against predators and are known to have both toxicological as well as pharmacological effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…Further, maintaining highdose chemotherapy in adults with osteosarcoma does not affect survival, histological response, recurrence, and time to recurrence [2]. Clinical trials have confirmed that combining cinobufacini injection with chemotherapy may enhance the effect of conventional therapies [3,4]. The use of cinobufacini injection in cancer patients might improve their quality of life.…”
mentioning
confidence: 99%